2001
DOI: 10.1159/000054288
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Prevents Fas-Induced Apoptosis in Lymphocytes through Modulation of Bcl-2 and Caspase-3

Abstract: Objective: Growth hormone (GH) has been reported to have a potent effect on the immune system. However, the detailed mechanism of the effect of GH on the immune system has not yet been clarified. This study was designed to investigate the nature of this mechanism. Methods: In the present study, we investigated the effects of GH on the susceptibility of both human CEM/C7 lymphocytes and human IM-9 lymphocytes to Fas-induced apoptosis. Results: Both cell lines expressed GH receptor mRNA. GH rescued Fas-induced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 40 publications
3
23
0
1
Order By: Relevance
“…Matsuda et al reported that GH down-regulated Fas expression on human neutrophils and inhibited the apoptosis [117]. Human GH reportedly diminished Fas-mediated cell death without changing Fas antigen by enhancing the expression of the anti-apoptotic oncoprotein Bcl-2 and depressing Fas-induced activation of the cysteine protease, caspase-3, using human T and B lymphocyte cell lines, promonocytic cell line, and human primary cultured monocytes [118,119]. GH protected human lymphocytes from irradiation-induced cell death by increasing Bcl-2 [120].…”
Section: Anti-apoptotic Effectmentioning
confidence: 99%
“…Matsuda et al reported that GH down-regulated Fas expression on human neutrophils and inhibited the apoptosis [117]. Human GH reportedly diminished Fas-mediated cell death without changing Fas antigen by enhancing the expression of the anti-apoptotic oncoprotein Bcl-2 and depressing Fas-induced activation of the cysteine protease, caspase-3, using human T and B lymphocyte cell lines, promonocytic cell line, and human primary cultured monocytes [118,119]. GH protected human lymphocytes from irradiation-induced cell death by increasing Bcl-2 [120].…”
Section: Anti-apoptotic Effectmentioning
confidence: 99%
“…Pankov [62] reviewed these and other studies that showed that lymphoid tissues including the spleen, thymus, lymph nodes and peripheral blood cells expressed GH, GHR and IGF-1, the downstream effector of GH. Thus, GH and PRL can act directly on hematopoietic cells including lymphocytes to mediate effects such as enhanced proliferation [63] [64] and/or inhibition of apoptosis, e.g., [65], [66], [67], [68].…”
Section: Distribution Of Gh and Prl Receptorsmentioning
confidence: 99%
“…Fas expression did not significantly change in the PMN from patients treated with hGH when compared with placebo-treated controls (data not shown), but hGH is known to down-regulate Fas expression in PMN in cell-culture experiments [17]. Further, rather than decreasing Fas expression, GH has been shown to prevent Fas-induced apoptosis in human leukocyte lines through an increase in BCL-2 a decrease in caspase-3 expression and activity [35].…”
Section: Discussionmentioning
confidence: 89%